The Category of Time in Musical Art - Demidova, Marina; Levytska, Irina; Novska, Olena (Journal of History Culture and Art Research, 2020)
The article defines the semantic relations inherent in the categories of “time” in the field of art, examines the phenomenon of time in music, based on the internal laws of creation and interpretation of the artistic image, as well as analyzes the temporal characteristics that affect the perception and understanding of the musical text. The article discusses the mechanism of realization of temporal characteristic of musical art, the style and time gradations of samples of musical art. The following properties of the time of the musical text (in the process of performance) are proposed: relevance, irreversibility, tightness, personification, existentiality. Common scientific principles of systematization and generalization directed on the classification of revealing of logical connections, common signs and qualities mentioned by scientists in definition of time have been used. The application of theoretical methods of research has been provided for (analyses, synthesis, comparison, idealization) that is provided for analyzing the main principles of time interpretation by Ukrainian and foreign scientists. It is necessary to find out the common-sense correlations and psychological aspects, which can influence on the perception of time in music. The paper defines the time properties of a musical composition (musical notation): tightness, fluidity, discretion, structurality, intellectual mediocrity, semantic meaning.